2011
DOI: 10.1603/en11167
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seston on Mortality of Simulium vittatum (Diptera: Simuliidae) From Insecticidal Proteins Produced by Bacillus thuringiensis subsp. israelensis

Abstract: Water was collected from a site on the Susquehanna River in eastern Pennsylvania, where less-than-optimal black fly larval mortality had been occasionally observed after treatment with Bacillus thuringiensis subsp. israelensis de Barjac insecticidal crystalline proteins (Bti ICPs). A series of experiments was conducted with Simulium vittatum Zetterstedt larvae to determine the water related factors responsible for the impaired response to Bti ICPs (Vectobac 12S, strain AM 65-52). Seston in the water impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 15 publications
(18 reference statements)
1
24
0
Order By: Relevance
“…Kaolinite clay is naturally occurring in many waterways. Iburg et al (2011) found that larval susceptibility to Bti ICPs was not significantly influenced by the presence of clay in the larval medium. Gray et al (2012) also found that larval susceptibility Fig.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Kaolinite clay is naturally occurring in many waterways. Iburg et al (2011) found that larval susceptibility to Bti ICPs was not significantly influenced by the presence of clay in the larval medium. Gray et al (2012) also found that larval susceptibility Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Pesticide applicators are instructed on the product label to apply the larvicide when the turbidity in a river is low. While this may increase efficacy in some cases, results from Experiment 2 and observations made by Iburg et al (2011) suggest that the components of the seston affect larvicide efficacy more than the turbidity of the water.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations